TEG's Utility to Detect Hypercoagulability in Adult Patients at Post-Cardiac Surgery Using Cardiopulmonary Bypass in ICU - Hildegardis Dyna Dumilah; Hartono Kahar; Arifoel Hajat; Philia Setiawan; Heroe Soebroto (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
The use of Cardiopulmonary Bypass (CPB) in adult patients of cardiac surgery disrupts the coagulation system. The mostcommon complication of the coagulation system is bleeding; however, that does not rule out the possibility of a dangeroushypercoagulation condition. A quick and precise coagulation test can provide clues for clinicians to predict futurehemostatic disorders or determine interventional therapy. aPTT and PT are standard laboratory tests, which are limited todetect a deficiency of coagulation factors. Thromboelastography (TEG) test (R time, K time, α angle, MA, and LY30) providesan overview of the entire coagulation and fibrinolysis process with faster results. A 2.7 mL citrate blood sample was takenand tested in a TEG®5000 device, then centrifuged. The plasma was then tested for aPTT and PT using the Sysmex CS-2100idevice. Bleeding volume was measured from chest drain 1-2 hours in the ICU after chest closure in the operating room.Bleeding criteria were as follows: > 1.5 mL/kg/hour for 6 hours consecutively in 24 hours or > 100 mL/hour. The resultsshowed 30 patients with no clinically significant bleeding. A significant correlation was found between PT and bleedingvolume at IV hour (p=0.008, r= 0.472). There was no correlation between aPTT and TEG (R time, K time, α angle, MA, andLY30) with the bleeding volume at I, II, III, and IV hours. There was a hypercoagulation indication of the TEG test of 56.7%,which showed clinical importance for the patient. PT can be used to analyze changes in bleeding volume at IV hour and TEGis more superior to detect hypercoagulability of adult patients after cardiac surgery with CPB.